Comparison of Prophylactic Versus Regular Use of Antibiotics in C-Section - Shabnam, Saima Muhammad Ali, Sadia Hanif, Yasmeen Ashraf, Irum Batool Hashmi, Nighat Afridi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to compare the effectiveness of prophylactic versus regular use of antibiotics. Study Design: Randomized Control Trial Place and Duration: In the department of Gynaecology and Obstetrics, Combined Military Hospital, Peshawar for the duration from January 2021 to December 2021. Methods: Total 116 pregnant women had age 20-48 years were included. All the patients were admitted to hospital and underwent for c-section. We have taken informed written consent of all females for detailed demographics included age, BMI, gestational age and parity. Patients were equally divided in two different groups. Group I received prophylactic antibiotic (Cefazolin 1g) and group II received cefuroxime 750 mg. Post-operatively outcomes were compared in terms of surgical site infection, hospitalization and other adverse events among both groups. SPSS 20.0 was used to analyze all data. Results: Among 116 cases, 58 (50%) females had age 20-30 years, 39 (33.6%) were aged between 31-40 years and 19 (16.4%) had age 41-48 years. 70 (60.3%) cases had BMI >25kg/m2 and 46 (39.7%) had BMI <25kg/m2. Majority of the cases 67 (57.8%) were emergency c-sections and 49 (42.2%) were elective cases. Mean gestational age of the females in group I was 37.2±11.91 weeks and in group II was 36.11±8.45 weeks. Mean parity in group I was 2.7±4.13 and in group II was 1.9±6.8.We found that frequency of SSI was lower in group I 3 (5.2%) as compared to group II in 7 (12.1%). Mean hospitalization in group I was lower 3.6±4.16 days as compared to group II 7.5±6.17 days. Febrile illness and endometritis was also higher in group II with p value <0.04. Conclusion: We concluded in this study that prophylactic antibiotic was affective and useful among patients undergoing c-section in terms of minimum SSI, hospital stay and adverse events as compared to regular antibiotics. Keywords: C-section, Prophylactic, Antibiotics, Adverse Events